2022
DOI: 10.2147/idr.s341392
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Viral Load Suppression After Enhanced Adherence Counseling Among HIV-Positive Adults in West Gojjam Zone, Amhara Region, Ethiopia

Abstract: Background Viral load suppression among people living with HIV is the main goal of antiretroviral therapy (ART). The most cause for high viral load is poor adherence to ART. World Health Organization (WHO) recommends intensive enhanced adherence counseling for people with a high viral load, which is greater or equal to 1000 RNA copies per mL and at least on treatment for six months. However, little is known about the outcome of enhanced adherence counseling. The study aimed to assess the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
8
15
4
Order By: Relevance
“…The overall incidence rate of viral load suppression was 9.68 per 100 person months (95% CI = 8.56, 10.94). This finding is lower than the incidence rate found in the study conducted in the study done in West Gojjam zone, Amhara region (11.17 per 100 person-months), 24 but higher than the study conducted in Kenya (3.9 per 100 person month). 11 The differences in socioeconomic status, quality of care provided, type of ART treatment regimen, ART treatment adherence level, and some co-morbidity might explain the variation in incidence rate among studies.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The overall incidence rate of viral load suppression was 9.68 per 100 person months (95% CI = 8.56, 10.94). This finding is lower than the incidence rate found in the study conducted in the study done in West Gojjam zone, Amhara region (11.17 per 100 person-months), 24 but higher than the study conducted in Kenya (3.9 per 100 person month). 11 The differences in socioeconomic status, quality of care provided, type of ART treatment regimen, ART treatment adherence level, and some co-morbidity might explain the variation in incidence rate among studies.…”
Section: Discussioncontrasting
confidence: 74%
“…The median time to viral load suppression was 9 months (95% CI: 8.22, 9.78). This was longer than studies conducted in Arbaminch hospital, Southern Ethiopia (3 months); 20 Oromia, Ethiopia (181 days); 21 west Gojjam zone, Amhara region (5 months) 24 and New York (50 days). 7 This difference in might be due to the difference in the quality of care, the patients’ behavior like adherence, and clinical characteristics of the patient.…”
Section: Discussionmentioning
confidence: 72%
“…Patients with a normal BMI (18.5-24.9kg/m 2 ), according to the WHO classi cation, were more likely to achieve viral load suppression, which is in line with the ndings of primary studies (18), this is because BMI has a predictive impact on immune recovery, which is crucial for controlling viral replication. Additionally, the baseline CD4 count of patients was found to determine virological suppression, which is consistent with previous studies (19,20). CD4 count plays a vital role in immune function, protecting the body against opportunistic infections and the multiplication of the virus.…”
Section: Discussionsupporting
confidence: 88%
“…The study found through database searching was performed between 2011 and 2022. Regarding the study area/region, seven studies were conducted in the Amhara region (19,24,25,26,27,28,29), six studies in the Oromia region (20,30,31,32,33,34), ve studies in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region (18,35,36,37,38), one study in the Tigray region (39) and two studies in the Addis Abeba city administration (40,41).…”
Section: Characteristics Of the Included Studies In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation